Proceedings of the 14th ACM / IEEE International Symposium on Empirical Software Engineering and Measurement (ESEM) 2020
DOI: 10.1145/3382494.3410632
|View full text |Cite
|
Sign up to set email alerts
|

Teamwork Quality and Team Success in Software Development

Abstract: Background: Teamwork is central component of any software development organization. Therefore, the assessment of teamwork quality is important for team management in practice. TWQ (Teamwork Quality) is a measure of the quality of intra-team interactions developed specifically for software development teams. Aims: To perform a differentiated replication of previous studies on TWQ to expand the contexts in which TWQ has been applied, to refine the measurement instrument, increasing its reliability and validity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
1
0
3
Order By: Relevance
“…Team: it includes the factors linked to team management, capabilities, and interactions that occur within a team. Team [24], [25], [27]- [29], [31], [33]- [41], [47], [50], [54], [56], [58] Work Environment Psychological safety Interaction between team members Communication Distance between team members Organization of the team Equipment Capabilities Technical debt Individual [35], [37], [44], [45], [47], [51], [52], [56] Soft Skills Technical Capabilities Motivation Organizational [26], [28], [35], [36], [42]- [44], [49], [56] Organizational Support Team management Personnel Management Individual training management Characteristics of leadership Characteristics of the projects Processes [16], [24], [30], [35], [36], [43], [52], [53], [56], [58] Quality SW development methods Techniques for the management of SW projects SW project management…”
Section: Data Extraction Resultsmentioning
confidence: 99%
“…Team: it includes the factors linked to team management, capabilities, and interactions that occur within a team. Team [24], [25], [27]- [29], [31], [33]- [41], [47], [50], [54], [56], [58] Work Environment Psychological safety Interaction between team members Communication Distance between team members Organization of the team Equipment Capabilities Technical debt Individual [35], [37], [44], [45], [47], [51], [52], [56] Soft Skills Technical Capabilities Motivation Organizational [26], [28], [35], [36], [42]- [44], [49], [56] Organizational Support Team management Personnel Management Individual training management Characteristics of leadership Characteristics of the projects Processes [16], [24], [30], [35], [36], [43], [52], [53], [56], [58] Quality SW development methods Techniques for the management of SW projects SW project management…”
Section: Data Extraction Resultsmentioning
confidence: 99%
“…Otro aspecto que influye en la forma de interacción dentro de un equipo es la experiencia en conjunto (Narayan et al, 2011) esta repercute en el equilibrio en las contribuciones realizadas por cada integrante y el prestigio que existe entre ellos (Mendes et al, 2018). En este sentido, el esfuerzo enfocado en efectuar de manera exitosa las tareas asignadas (Batista et al, 2020), y la mala vinculación que pudieran tener (Anwar et al, 2018) afectan a la productividad, como así también la motivación compartida por el equipo (Fagerholm et al, 2015;Lindsjørn et al, 2016;Oliveira et al, 2016) y los modelos mentales (Bezerra et al, 2020); es decir, el conocimiento en común que poseen. Resulta fundamental considerar la interacción en equipos formados por miembros provenientes de diversas culturas ya que se ha identificado que pueden surgir dificultades al no comprender la cultura ajena (Anwar et al, 2018) lo que afecta también la confianza entre los miembros del ET.…”
Section: El Detalle Del Análisis Completounclassified
“…En el Manifiesto Ágil (Beck, 2001) se establece su importancia, entre los miembros del equipo y con el resto de los individuos involucrados. Frameworks como XP (Beck & Andres, 2004) y Scrum (Sutherland, 2014) proponen prácticas que se basan en una comunicación honesta y directa en el equipo, tanto intra-equipo (Batista et al, 2020;Fatema & Sakib, 2018;Mendes et al, 2018) como con clientes (Qahtani, 2020), incluyendo la comunicación cara a cara (Mendes et al, 2018) o de forma remota (Oliveira et al, 2016). Un factor relacionado con esto es la distancia entre los miembros, ya sea geográfica o temporal (Narayan et al, 2011;Santos et al, 2016;Wagstrom & Datta, 2014).…”
Section: El Detalle Del Análisis Completounclassified
See 1 more Smart Citation
“…Research has shown that TWQ has a positive impact on team development [6], [7], and is, consequently, essential for succeeding with ASD [8], [9], [10], [11], [12]. Batista et al [13] discussed that the effective combination of individual parts, often carried out by software development teams, requires interactions among team members and the coordination of interdependent individual and team level tasks. Given its impact, researchers argued about the importance of assessing TWQ to increase the chances of succeeding with ASD [13], [14].…”
Section: Introductionmentioning
confidence: 99%